Peran Kepemimpinan Pangeran Sabakingking dalam Penyebaran Islam di Banten (1552-1570) - Supendi, Usman; Suprianto, Sopian (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Banten Sultanate was an Islamic kingdom founded by Prince Sabakingking, another name for sultan Maulana Hasanudin in the 16th century on the west coast of Java. Banten Sultanate became one of the centers of Islamic power in West Java and played an important role in the spread of Islam in the archipelago. This research aims first, to know the history of the formation of Banten Sultanate, second, to reveal the strategy of spreading Islam in Banten during the leadership of Prince Sabakingking, third, to describe the development of Islam in Banten during the leadership of Prince Sabakingking. The method used in writing this article is using historical research method through four stages. The stages are heuristics, criticism (external and internal), interpretation, and the last is writing or historical reconstruction (historiography). This research found that the Sultanate of Banten, founded by Maulana Hasanuddin in the 16th century, was one of the important Islamic kingdoms in the archipelago. The sultanate’s beginnings were linked to the expansion of the influence of the Demak Kingdom, which sought to control trade routes and end the dominance of the Sunda Kingdom. Pangeran Sabakingking played a central role in building the foundation of Islamic power in Banten, which was marked by the transfer of the center of government to Surosowan and the development of important infrastructure, such as the Great Mosque of Banten and a port that supported trade activities. Through a strategy of spreading Islam that involved ulama and strengthening the economy, Banten succeeded in becoming a center for international trade and the spread of Islam, as well as integrating Islamic teachings into the social and political structure of society.